LEGAL PROTECTION AND LEGAL RESPONSIBILITY OF UNIT LINK LIFE INSURANCE AGREEMENTS - Andri Purnama, Tubagus; Ratnawati Gultom, Elfrida (UNES Law Review, 2022)
Along with the progress of modern industry and the economy, the development of business in the insurance sector is increasingly having a positive impact. The concept of insurance activity gave birth to many large industrial companies engaged in the insurance business and expanded to various types of risk coverage and products, one of which is life insurance. Apart from being an instrument that acts as a risk bearer, the insurance industry also plays an important role in the development of the Indonesian economy. One of its functions is to act as a financial planner. To meet the needs of the community, the life insurance industry in Indonesia has developed its products into investment-linked insurance or currently known as unit-linked products. Unit link products can provide solutions that suit the needs of society, thereby enabling consumers to obtain various benefits, namely protection and investment. It is not uncommon in practice to find various discrepancies with legal norms, both from the client's and the company's point of view. This study discusses the form of legal protection for unit link insurance insureds at life insurance companies with Wanaartha and to know and understand the position of insurance companies in carrying out unit link insurance activities according to applicable regulations.